THE DIDACTIC PROCESS OF THE TRANSMISSION OF THE BARIS PAKU DANCE AS A MEANS OF STRENGTHENING CHARACTER EDUCATION AMONG YOUNG GENERATIONS IN BANJAR ADAT SABANG, KINTAMANI - I Kadek Indrawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the inheritance process, cultural meaning, and educational values embedded in the Baris Paku Dance as a sacred traditional dance developed in Banjar Sabang, Selulung Indigenous Village, Kintamani District, Bangli Regency, Bali. The research is motivated by the importance of preserving local cultural heritage amid contemporary developments, as well as the role of the Baris Paku Dance as a medium for character formation among the younger generation through customary systems still practiced by the local community. The research focuses on the historical background of the Baris Paku Dance, its form and structure, the cultural inheritance process, and the implementation of educational values in community life. This research employs a qualitative approach with ethnographic methods. Data was collected through participatory observation, in-depth interviews, documentation, and literature reviews. The findings show that the Baris Paku Dance is a sacred dance born from the spiritual traditions of the Banjar Sabang community as a means of purification and balancing the relationship between the sekala (visible) and niskala (invisible) realms. The dance inheritance is carried out through the Megama Truna system, enabling the transfer of knowledge, skills, cultural values, and social responsibility to younger generations. The Baris Paku Dance encompasses religious, social, aesthetic, cultural, and character values that play an important role in shaping the identity and strengthening the character of the Banjar Sabang community.